Μ-Opioid receptor activation prevents acute hepatic inflammation and cell death. Issue 7 (13th February 2007) - Chakass, Dania; Philippe, David; Erdual, Edmone; Dharancy, Sébastien; Malapel, Mathilde; Dubuquoy, Caroline; Thuru, Xavier; Gay, Jerome; Gaveriaux-Ruff, Claire; Dubus, Pierre; Mathurin, Philippe; Kieffer, Brigitte L; et al.
Abstract : Background and aims: The detrimental impact of opioid agonist on the clinical management of inflammatory diseases remains elusive. Given the anti-inflammatory properties of the μ-opioid receptor (MOR) agonists at the intestinal barrier, we hypothesised that MOR activation might also dampen acute hepatic inflammation and cell death—major determinants in the pathogenesis of liver diseases. Patients and methods: The expression of MOR in liver biopsy specimens and peripheral blood mononuclear cells of untreated patients with chronic hepatitis C virus infection and controls, primary hepatocytes and cell lines was determined by quantitative PCR, immunoblotting and/or immunohistochemistry. The effects of peripheral MOR agonist (d -Ala2, NMe-Phe4, Gly5-ol (DAMGO)) and/or antagonist (naloxone methiodide) were explored in two models of acute hepatitis in mice. MOR-deficient mice were used to evaluate the essential regulatory role of MOR during carbon tetrachloride (CCl4 )-induced hepatitis. The role of DAMGO in cell death was investigated using terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling (TUNEL) analysis and quantification of lactate dehydrogenase release. Results: The key role of MOR in the prevention of acute hepatic inflammation and cell death in vivo and in vitro is reported. Whereas MOR gene expression increased transiently in the model of acute liver injury and TNFα-treated HepG2 cells, an impaired expression of MOR mRNA in human chronic hepatitis C samples was found. Furthermore, preventive administration of the selective MOR agonist DAMGO enhanced hepatoprotective-signalling pathways in vivo that were blocked by using naloxone methiodide. Consistently, genetic and pharmacological inhibition of MOR enhanced the severity associated with experimental hepatotoxin-induced hepatitis. Finally, treatment with DAMGO was shown to prevent cell death in vitro in HepG2 cells in a MOR-dependent manner and to prevent concanavalin A- and CCl4 -induced cell death in vivo, providing a possible explanation for the anti-inflammatory role of MOR activation in the liver. Conclusions: The results indicate that MOR agonists may prevent acute hepatitis and hold promising therapeutic use to maintain remission in both chronic inflammatory bowel and liver diseases.